Jornalismo e literatura na obra Notícia de um sequestro, de Gabriel García Márquez - Signor, Bruna (2018)
The present study analyzes the book Notícia de um Sequestro (1996), which was written by the Colombian writer and journalist Gabriel Garcia Marquez. The relevance of this work for the study is in the fact that it uses Literature and Journalism in its narration. This literary genre makes a journalistic fact turns into a surrounding and humanized narrative making the by means of mixing journalism and fiction. The research focus on this book with the aim to investigate how the author used the journalistic and literary language and how both helped to develop this plot, in which he tells the kidnapping of ten journalists and relatives of influent politicians in Colombia by the Extraditable group, a group of drug traffickers who were led by Pablo Escobar, who feared the extradition to the United States. Garcia Marquez book contributed to demystify the story known as official by the government and the meadia of communication of that time. The applied methodology was the bibliographic research which was fulfilled by t to understand how he used Literary Journalism in other moments of his career. Besides other were used to treat about the aspects related to the narrative, Lopes (2010) who elucidates the distinctions between journalistic and literary genres, Barbosa (2007) who articulates about Journalism and Literature and finally some authors like Gilard (2006), Gardner (1995) and Silva (1990) who were important to explain how Garcia Marquez used these two trends in his previous works. The result of the analysis is the confirmation that the author was successful when he joined Journalism and Literature in a way that both, despite their specificities, can complement each other to build it and reaffirm this literary genre.